Systematic review: the prevention of oesophageal stricture after endoscopic resection. Issue 1 (17th May 2015) - Barret, M.; Beye, B.; Leblanc, S.; Beuvon, F.; Chaussade, S.; Batteux, F.; Prat, F.
Summary Background Extensive endoscopic resections for the treatment of early oesophageal neoplasia can result in fibro‐inflammatory strictures that require repeated interventions, which significantly alter the patients' quality of life. Aims To review current evidence about the prevention of oesophageal strictures following endoscopic resections. Methods Systematic search of PubMed and Embase from inception to March 2015 using appropriate keywords. All original publications in English were included, and articles on the treatment of oesophageal stricture were excluded. Results Of the 461 hits, 62 studies were included in the analysis. Among the wound‐protective strategies, polyglycolic acid sheets showed the most convincing evidence with a 37.5% stricture rate and excellent safety. Regenerative medicine, using cell sheets of autologous keratinocytes, resulted in a 25% stricture rate, although with cost and availability concerns. Among anti‐proliferative treatment modalities, steroid treatment, either endoscopically injected triamcinolone in the resection wound or orally administered prednisolone, proved effective with an overall stricture rate of 13.5%, with safety concerns regarding late oesophageal perforations and infectious morbidity. Among mechanical treatment options, poorly effective and high‐risk preventive balloon dilation tend to be replaced by prophylactic covered stent, with 18–28% stricture rates. Conclusions Although oral or locally injected steroids are promising options, no currently available technique is sufficiently efficient and devoid of significant safety concerns to recommend its routine use for the prevention of strictures after extensive endoscopic resection. Improving our knowledge in the mechanisms of oesophageal wound healing will guide the development of novel methods for stricture prevention.